Headmaster's instructional leadership, emotional intelligence and teacher's commitment in primary schools - Chinna Thambi, Kasturi Telagam; Lope Pihie, Zaidatol Akmaliah (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
This conceptual paper was develop to create a conceptual model in exploring the relationship between headmasters instructional leadership practices, emotional intelligence level and teacher’s commitment in primary school in Perak State. It is based on three theories; Instructional Leadership Theory, Emotional Intelligence Theory, and Teacher’s Commitment Theory. Ten dimensions of Instructional Leadership styles (Philip Halliger, 1995), five dimensions of Emotional Intelligence (David Goleman, 2001), and four factors of teacher’s commitment (Allen Meyer, 1991) are identified to construct the model.